Impact of Digital Marketing on Business Growth in Nepal - Thakur, Saroj Kumar (Journal of Nepal Commerce Association, 2025)
Digital marketing has transformed business practices worldwide, including in Nepal, driven by the widespread adoption of the internet and smartphones. Over the past decade, Nepal’s digital landscape has evolved rapidly, marked by increased internet penetration, improved connectivity, and the growing use of digital payment systems. These developments have enabled businesses to expand market reach, enhance customer engagement, and acquire new customers through technology-enabled platforms. This study examines the impact of digital marketing on business development in Nepal by analyzing its key benefits, including cost-effectiveness, brand awareness, and customer interaction. It also explores major challenges faced by Nepalese businesses, such as limited technological knowledge, inadequate access to digital devices, and cultural considerations that require localized marketing approaches. By investigating how startups and established organizations utilize digital tools—such as search engines, social media, and email marketing— the study provides insights into consumer behavior and emerging market trends in Nepal. Furthermore, the research assesses the future prospects of digital marketing in the context of rapid technological change and shifting consumer preferences. The study emphasizes the importance of adopting innovative, data-driven strategies to remain competitive and offers recommendations for businesses, policymakers, and researchers seeking to harness the potential of digital marketing in Nepal’s dynamic business environment.